Synthesis of Functional Groups on Surface-Modified Activated Carbon for Nitrate Removal from Tofu Home Industry Wastewater - Dini Aprilla; Indah Permata Sari; Chairul Irawan; Abubakar Tuhuloula; Iryanti Fatyasari Nata; Ariani Ariani; Muhammad Dody Isnaini (Jurnal Teknik Kimia dan Lingkungan, 2026)
This research successfully converted spent coffee grounds (SCG) into powdered activated carbon (AC) through carbonization at 400°C. The surface functional groups of this carbon were subsequently modified using hydrochloric acid as an activating agent to enhance its adsorption properties. The purpose of this research was to evaluate the performance of this modified activated carbon (MAC) as an adsorbent for reducing nitrate content in tofu industry wastewater, which is characterized by high concentrations of nitrate ions. The MAC was characterized using SEM and FTIR analysis to determine its surface morphology and functional groups, which are critical for adsorption process of capturing atoms, ions, and molecules on a materials surface. The batch adsorption experiments using AC and MAC as adsorbent were then performed for reducing nitrate content in tofu industry wastewater. Batch adsorption experiments were conducted under optimal conditions: a pH of 7±0.2, room temperature, a stirring rate of 150 rpm, and an adsorbent dose of 1 g/L. The results demonstrated a significant decrease in nitrate concentration from 28.6 mg/L to 1.2 mg/L, achieving a 95.80% removal efficiency at an equilibrium contact time of 180 minutes. The performance of the MAC was comparable to, and even more favorable than, that of unmodified activated carbon (UAC) used as a control that only achieved 58.74% percentage removal of nitrate. This remarkable nitrate removal efficiency is attributed to the distinct morphology and enhanced surface properties imparted by the hydrochloric acid modification. Therefore, modified activated carbon from coffee grounds shows high potential as an effective adsorbent for wastewater treatment.